UAN: underwater acoustic network - Caiti, A. (2012)
Acoustic networks are for underwater what wifi is for terrestrial networks. The ocean is a nearly perfect media for acoustic waves in which regards long range propagation but poses a number of challenges in terms of available bandwidth, Doppler spread and channel fading. These limitations originate in the physical properties of the ocean, namely its anisotropy and boundary interaction which are particularly relevant in coastal waters where acoustic propagation becomes predominantly de- pendent on seafloor and sea surface properties. The acoustic communication channel is therefore multipath dominated and time and Doppler spread variable. The problem is aggravated when involving moving receivers as for instance when attempting to establish communication with or between moving autonomous underwater vehicles. The EU-funded project UAN - Underwater Acoustic Network aims at conceiving, developing and testing at sea an innovative and operational concept for integrating in a unique communication system submerged, surface and aerial sensors with the objective of protecting off-shore and coastline critical infrastructures. UAN went through various phases, including the development of hardware and software specific components, its testing independently and then in an integrated fashion, both in the lab and at sea. This paper reports on the project concept and vision as well as on the progress of its various development phases and the results obtained herein. At the time of writing, a final project sea trial is being planned and will take place two weeks before the conference so, although here we will concentrate on the progress obtained so far, the presentation at the conference may include additional results depending on the outcome of the sea trial.